(untitled) (Research, Society and Development, 2021)
The main objective of this article is to bring paradidactic / literature books as a pedagogical tool to be used by Chemistry teachers in high school, in order to help teachers increase their pedagogical background, facilitating the way of transmitting content and highlighting the its students how scientific discoveries, facts and myths occur in fantasy books, using as an example the pseudoscience that was alchemy. In-depth qualitative research was carried out on books, whose main theme was related to fantasy and useful in teaching. The choice on the horizon of the magician, the fantastic, the fantasy, was due to an increase in the imaginative capacity provoked when reading works of this nature, and due to the linguistic ease with which high school students are familiar, a language that approach reading and let them emerge in the world of imagination and creativity. At the end of the article, we can highlight the little use of paradidactic books / literature in diverse areas of teaching.